The Influence of Climate Change on the Spread of Infectious Diseases in Coastal Regions - Siregar, Okkis Razuansyah; Sari, Siti Kemala; Kosasih, Edward (ScieClouds Publishing, 2025)
Climate change has significantly influenced the spread of infectious diseases, particularly in coastal regions where rising temperatures, increased precipitation, and extreme weather events create favorable conditions for disease transmission. This study examines the relationship between climate change and the prevalence of vector-borne and waterborne diseases in coastal communities, addressing gaps in previous research that primarily focused on macro-level epidemiological trends. Using a quantitative approach, data were collected from multiple coastal regions, analyzing climate variables and disease incidence rates. The findings reveal a strong correlation between increasing temperatures and the expansion of disease vectors such as mosquitoes, contributing to higher cases of malaria and dengue fever. Additionally, poor drainage systems and inadequate sanitation were found to exacerbate the spread of cholera and typhoid fever. While community-driven adaptation strategies—such as improved water storage and mosquito control—play a role in mitigating risks, institutional responses remain fragmented, limiting long-term disease prevention efforts. This study underscores the urgent need for climate-resilient public health infrastructure, decentralized early warning systems, and the integration of public health and climate adaptation policies to reduce disease outbreaks in vulnerable coastal populations. Future research should explore longitudinal data on climate-disease interactions and assess the effectiveness of policy-driven interventions. The findings contribute to a deeper understanding of how climate change exacerbates public health risks and highlight the necessity for proactive, evidence-based strategies to enhance resilience in coastal regions.